2015
DOI: 10.1159/000438930
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cell Membrane Antigens in Cells Excreted in the Urinary Sediment Predicts Progression of Renal Disease in Patients with Focal Segmental Glomerulosclerosis

Abstract: Background/Aims: A link between the number of podocytes excreted in the urine and activity of glomerular disease has been established. The aim of this study was to investigate possible correlations between urinary cells' phenotype and the progression of focal segmental glomerulosclerosis (FSGS). Methods: Forty patients with newly diagnosed FSGS were included. Cells were isolated from urine by adherence to collagen-coated cover slips and assessed for the expression of podocalyxin (PDX), CD68 and Ki67 antigens b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Glomerulosclerosis is characterized by loss of glomerular cells, increased synthesis of extracellular matrix of the glomerulus, and reduced Fig. 3 Renal survival curve analysis in both groups (Kaplan-Meier survival analysis) Table 5 Cox regression analysis of glomerular sclerosis proportion in renal prognosis of patients with IMN The composite endpoint was defined as a 20% reduction in the eGFR or development of ESRD Model 0: Unadjusted Model 1: was adjusted for age, gender, BMI, systolic blood pressure (BP), Immunosuppressant Model 2: was adjusted for model 1plus serum creatinine, 24-h urinary protein Model 3: was adjusted for mode 2 plus renal interstitial inflammatory cell infiltration, renal tubular atrophy, renal degradation, resulting in excessive accumulation of extracellular matrix [7,15,16]. Dumoulin et al [17] hypothesized that the deposition of immune complexes on the glomerular epithelial side leads to the detachment of glomerular podocytes and glomerular basement membrane, resulting in glomerular segmental sclerosis and sclerosis [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerulosclerosis is characterized by loss of glomerular cells, increased synthesis of extracellular matrix of the glomerulus, and reduced Fig. 3 Renal survival curve analysis in both groups (Kaplan-Meier survival analysis) Table 5 Cox regression analysis of glomerular sclerosis proportion in renal prognosis of patients with IMN The composite endpoint was defined as a 20% reduction in the eGFR or development of ESRD Model 0: Unadjusted Model 1: was adjusted for age, gender, BMI, systolic blood pressure (BP), Immunosuppressant Model 2: was adjusted for model 1plus serum creatinine, 24-h urinary protein Model 3: was adjusted for mode 2 plus renal interstitial inflammatory cell infiltration, renal tubular atrophy, renal degradation, resulting in excessive accumulation of extracellular matrix [7,15,16]. Dumoulin et al [17] hypothesized that the deposition of immune complexes on the glomerular epithelial side leads to the detachment of glomerular podocytes and glomerular basement membrane, resulting in glomerular segmental sclerosis and sclerosis [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20% of patients with IMN progress to end-stage renal disease within 5-15 years or die from related complications [3][4][5]. In recent years, the morphological changes of renal tissue and glomerulosclerosis have gradually attracted attention as the influencing factors of prognostic evaluation of patients with IMN, but significant differences in their research conclusions are observed [5][6][7][8]. IMN pathology related with glomerulosclerosis is closely associated with the patient's prognosis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the number of glomerular proliferating cells is a more sensitive parameter that can be related to albuminuria rather than to histology in the 2 tested models of glomerular scarring, as was suggested recently for proliferating cells in the urine of FSGS patients. 47 The number of glomerular proliferating cells also was related to cortical collagen I expression in both models. Notably, collagen IV is the type of collagen expressed in both normal and diseased glomeruli (sclerosis), whereas collagen I is normally not expressed in the glomerulus, but several studies have shown glomerular collagen I expression in various glomerulopathies.…”
Section: Discussionmentioning
confidence: 86%
“…35,36 It was soon demonstrated that assessment of podocyte antigen expression immediately after the recovery of the cells from urinary sediment by adhesion to a plastic surface provides a useful tool to investigate the importance of podocytes in the progression of glomerular diseases. 37 The concentration of proteins secreted to the urinary space by damaged podocytes can be measured using the western blot technique. In patients with diabetes, the urinary podocalyxin concentration is higher than the cut-off value in patients at the normoalbuminuric, microalbuminuric and macroalbuminuric stage.…”
Section: Methods Of Quantitative and Qualitative Assessment Of Podocymentioning
confidence: 99%